Electron beam irradiation effects on ethylene-tetrafluoroethylene copolymer films - Nasef, Mohamed Mahmoud (Elsevier Ltd., 2003)
The effects of electron beam irradiation on ethylene-tetrafluoroethylene copolymer (ETFE) films were studied. Samples were irradiated in air at room temperature by a universal electron beam accelerator for doses ranging from 100 to 1200kGy. Irradiated samples were investigated with respect to their chemical structure, thermal characteristics, crystallinity and mechanical properties using FTIR, differential scanning calorimeter (DSC) and universal mechanical tester. The interaction of electron irradiation with ETFE films was found to induce dose-dependent changes in all the investigated properties. A mechanism for electron-induced reactions is proposed to explain the structure-property behaviour of irradiated ETFE films. Â© 2003 Elsevier Ltd. All rights reserved.